ANALISA PENGARUH MOTIVASI KERJA TERHADAP PRESTASI KERJA DOSEN PADA SEKOLAH TINGGI ILMU EKONOMI AAS - Wikan Budi Utami (ITB AAS INDONESIA Surakarta, 2017)
The purpose of this study is to determine the relationship between work motivation with the performance of lecturer at the College of Economics AAS (STIE-AAS). The motivation factor used in this research is based on the five human needs according to Maslow, namely physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs. The population in this study are lecturers STIE-AAS who actively teach at the time this research is done. This research was conducted in the even semester of academic year 2015/2016 in March-April 2016. The technique of determining the sample in this study is to use purposive sampling. The sample in this research is: STIE-AAS lecturer who in the even semester of Academic Year 2015/2016 actively teaches. The type of instrument used in this study, namely questionnaires. To test whether the list of questionnaires that are made, valid (valid) and reliable (reliable) then used two test tools of the test validity and reliability test. This t test is used to examine the influence of each independent variable (physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs) to the dependent variable (STIE-AAS lecturer work achievement). The statistical test F aims to examine the effects of all independent or independent variables (physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs) together with dependent or dependent variables (STIE-AAS lecturer work achievement). This test is done by SPSS 17. Test R2 (Coefficient of determination) is done to find out how much influence the variable of physiological needs, the need of sense of security, social needs, self-esteem needs, and self-actualization needs towards the work performance variable of STIE-AAS lecturer. From the result of t test, it is known that the need for security and self-esteem need to be partially significant to the performance of STIE-AAS lecturers. While the physiological needs, social needs and self-actualization needs no significant effect on the performance of lecturers STIE-AAS. From the results of F test, it is known that physiological needs, safety needs, social needs, self-esteem needs, and self-actualization needs simultaneously have a significant effect on the performance of STIE-AAS lecturers. From result of test of R2 obtained coefficient value of determination equal to 0,639 which mean 63,9% achievement of lecturer work influenced by factors which resear in this research.